PENEGAKAN HUKUM ATAS PENEBANGAN HUTAN SECARA LIAR: MASALAH DAN SOLUSI - Radiah, Aisyatur; Pramono, Agus (Jurnal Magister Hukum Perspektif, 2025)
Illegal logging is a global problem that causes serious environmental damage, ranging from deforestation, biodiversity loss, to increased carbon emissions. Indonesia, as one of the countries with the largest tropical forests in the world, faces great challenges due to this practice, especially due to weak law enforcement and not optimal stakeholder involvement. The problems raised are (1) What are the main factors that cause illegal logging to occur, and (2) How is law enforcement against illegal logging activities in Indonesia. The objectives of this paper are (1) to find out what factors cause the occurrence of illegal logging criminal acts and (2) to find out the law enforcement against illegal logging activities in Indonesia. The type of research used is normative juridical with statutory and conceptual approaches. The results of this study are (1) Factors that cause illegal logging criminal acts to occur are due to economic, social, and political factors, (2) Law enforcement against illegal logging activities is regulated in the UUPPLH and the Law on Prevention and Eradication of Forest Destruction as well as legality verification by KLHK. In addition to these regulations, other efforts are still needed to optimize law enforcement on illegal logging. Keywords: Illegal logging, law enforcement, environment, criminal offense